Parents satisfaction with the services quality of Bangladesh International School & College (BISC) - Soneya, Rumnaz Asfin Ali (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2019.